IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING DALAM PEMBELAJARAN MATEMATIKA DENGAN MEDIA CANVA KELAS V - Ai Tresna Candani; Sandi Budiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research investigates the implementation of culturally responsive teaching (CRT) using Canva media to improve the mathematics learning outcomes of fifth-grade students at SDN Layungsari 2. The problem addressed in this study is the difficulty that students often face in understanding abstract mathematical concepts, especially when the teaching does not integrate the cultural context of the students. The objective of this research is to explore how the integration of CRT and digital media, particularly Canva, can enhance students' understanding and engagement in mathematics. A quasi-experimental method with a control and experimental group was used. The experimental group received learning with CRT and Canva, while the control group experienced traditional teaching methods. Data were collected through classroom observations, interviews, and documentation analysis. The results show a significant increase in the post-test scores of the experimental group compared to the control group. The N-Gain analysis revealed that the experimental group achieved higher improvement in their mathematical understanding. This indicates that the integration of culturally responsive teaching with Canva media is effective in making mathematical learning more relevant and engaging for students. These findings contribute to the growing body of research on culturally responsive teaching and technology integration in education.